Ailanthone blocks mitophagy to promote mtDNA leakage through BAX-BAK1 pores and suppress hepatocellular carcinoma cell proliferation - Qin, Yan; Gao, Ying; Wu, Dan; Liu, Qing-Qing; Su, Chang; Liu, Guan; Yang, Le; Zhao, Ming-Gao; Yao, Jing-Yue (Frontiers in Pharmacology, 2024)
Hepatocellular carcinoma (HCC), the third leading cancer mortality worldwide, shows rising incidence. The mitochondria in HCC cells are prone to damage from metabolic stress and oxidative stress, necessitating heightened mitophagy for mitochondrial homeostasis and cell survival. Thus, mitophagy inhibition is a promising HCC therapy. The traditional Chinese medicinal herb ailanthone have proved promote mitochondrial dysfunction and inhibits HCC. However, the underlying mechanism remains unclear. In this study, we demonstrated the potent anti-HCC properties of ailanthone and revealed its molecular mechanism. In vitro studies demonstrated that ailanthone effectively inhibited PINK1-PRKN-mediated mitophagy and promoted BAX-BAK1 mitochondrial pores formation through PRKN inhibition. This process led to the mitochondrial DNA (mtDNA) leakage into the cytoplasm, which subsequently triggered the induction of inflammatory factors. The inhibition of mitophagy and the activation of inflammatory response ultimately led to HCC proliferation inhibition. In vivo studies demonstrated that ailanthone exhibited stronger anti-HCC activity than 5-Fluorouracil (5-FU), with no significant adverse effects on animal body weight or the physiological functions of vital organs. In conclusion, this study highlighted the efficacy of ailanthone against HCC and elucidated its underlying molecular mechanisms, suggesting the promising therapeutic potential of ailanthone for HCC.